Microhabitat selection of Discocotyle sagittata (Monogenea: Polyopisthocotylea) in farmed rainbow trout - Rubio-Godoy, Miguel (Folia parasitologica, 2008)
Microhabitat preference of the monogenean Discocotyle sagittata (Leuckart, 1842) was determined in late spring and late autumn in rainbow trout, Oncorhynchus mykiss (Walbaum), reared in the Isle of Man, U.K. Discocotyle sagittata exhibits a preference for attachment to anterior gill arches: 29% of all worms occurred on gill arch I, 28% on II, 25% on III and 18% on IV. This distribution pattern on the introduced salmonid species is the same as reported for its native European host, the brown trout Salmo trutta (L.). Previous experimental work suggested that invasion is a passive process followed by post-invasion migration to anterior gill arches; the present work provides evidence of equivalent site selection taking place in fishes maintained under conditions promoting continuous reinfection in aquaculture. Migration may be density-dependent, since a significant inverse association was found between the intensity of mature parasites and their proportion on anteriormost gill arch I.
Keywords: Animals; ekosystém; Trematoda; nemoci ryb; Ecosystem; United Kingdom; Oncorhynchus mykiss; Gills; zvířata; Host-Parasite Interactions; Fish Diseases; infekce červy třídy Trematoda; interakce hostitele a parazita; Spojené království; žábry; Trematode Infections